Cardinal Isidore (c. 1390-1462) - Philippides, Marios, 1950- author.
1 online resource (xii, 421 pages)
Keywords: "A member of the imperial Palaeologan family, albeit most probably illegitimate, Isidore became a scholar at a young age and began his rise in the Byzantine ecclesiastical ranks. He was an active advocate of the union of the Orthodox and Catholic Churches in Constantinople. His military exploits, including his participation in the defence of Constantinople in 1453, provide us with eyewitness accounts. Without doubt he travelled widely, perhaps more so than any other individual in the annals of Byzantine history: Greece, Asia Minor, Sicily, Russia, Poland, Lithuania, and Italy. His roles included diplomat, high ecclesiastic in both the Orthodox and Catholic Churches, theologian, soldier, papal emissary to the Constantinopolitan court, delegate to the Council of Florence, advisor to the last Byzantine emperors, metropolitan of Kiev and all Russia, and member of the Vatican curia.This is an original work based on new archival research and the first monograph to study Cardinal Isidore in his many diverse roles. His contributions to the events of the first six decades of the quattrocento are important for the study of major Church councils and the fall of Constantinople to the Ottoman Turks. Isidore played a crucial role in each of these events."--Provided by publisher.